A Shifting Paradigm and Growth Strategies Reappraisal in Post-Crisis Asia - Koh, Winston T.H. (Institutional Knowledge at Singapore Management University, 2010)
The Financial Crisis of 2007 has had far-ranging implications for the global economy. Questions were raised if export-led growth model in Asia has hit the limits. Income growth must be inclusive and sustainable, and to be achieved alongside other goals. Asian economies need to rebalance growth toward greater reliance on domestic and regional demand with a greater emphasis on social and environmental sustainability.